Diagnosis and Management of Pulmonary Arterial Hypertension - Jeanne Houtchens; Douglas Martin; James R. Klinger (Pulmonary Medicine)
Pulmonary arterial hypertension is a rare disease, which requires a high index of suspicion to diagnose when patients initially present. Initial symptoms can be nonspecific and include complaints such as fatigue and mild dyspnea. Once the disease is suspected, echocardiography is used to estimate the pulmonary arterial (PA) pressure and to exclude secondary causes of elevated PA pressures such as left heart disease. Right heart catheterization with vasodilator challenge is critical to the proper assessment of pulmonary hemodynamics and to determine whether patients are likely to benefit from vasodilator therapy. Pathologically, the disease is characterized by deleterious remodeling of the distal pulmonary arterial and arteriolar circulation, which results in increased pulmonary vascular resistance. In the last fifteen years, medications from three different classes have been approved for the treatment of pulmonary arterial hypertension. These include the prostanoids, endothelin receptor antagonists, and phosphodiesterase-5 inhibitors.